Perancangan Sistem Informasi Pendataan Bantuan Penerima Hewan Ternak Pada Dinas Peternakan Kabupaten Nabire Menggunakan Metode Spiral - Gunawan Prayitno; Jenny Tandi; Arief Rahman Hakim (STMIK Pesat Nabire, 2024)
In an era of rapid development of science and technology, the use of information technology is crucial in improving efficiency and quality of services in various sectors, including the Nabire Regency Animal Husbandry Service. In this context, problems such as lack of effectiveness in providing livestock assistance and manual data management are the main challenges faced. This article discusses the need to develop an information system to increase efficiency and accuracy in managing data on recipients of livestock assistance. The Spiral Method was chosen as an approach in system development, combining an iterative and systematic nature to overcome the problems faced. It is hoped that advances in information and communication technology can provide solutions for the Nabire Regency Livestock Service in overcoming this challenge, as well as improving services to the community. it is hoped that the Nabire Regency Livestock Service can improve the process of providing livestock assistance according to predetermined targets and improve the quality of data management. This progress will have a positive impact on the welfare of the livestock farming community in the region. Apart from that, the use of information systems is also expected to be able to overcome problems such as overcrowded office storage cupboards and the risk of data loss or damage caused by manual management. Thus, this article not only highlights the challenges faced by the Nabire Regency Livestock Service, but also provides insight into solutions that can be implemented to improve efficiency and quality of service in data management and livestock assistance,